Trade effects of carbon pricing policies - Antonia Kurz; Stela Rubínová (World Trade Organization (WTO), 2024)
Policies that affect t he c ost o f u sing f ossil f uels i n p roduction h ave a complex impact on the economy. In this paper, we focus on the role of these policies for the pattern of comparative advantage through their effect o n p roduction c osts in manufacturing industries. Using data on carbon prices and fossil fuel subsidies, we show that less stringent carbon pricing policies increase comparative advantage in carbon intensive industries. In the first step, we use a fixed-effects gravity model of trade to estimate the export capabilities that determine the pattern of comparative advantage. In the second step, we regress the change in export capability of a country in an industry on the change in the country's carbon pricing policy, interacted with the carbon intensity of the industry, controlling for country and industry fixed effects. O ur r esults s uggest t hat a 1 0% i ncrease i n c arbon p rice i s a ssociated with a decline in export capability in the most carbon-intensive industry by 0.3% to 0.7%. On the other hand, industries with low carbon intensity are barely affected. Overall, we estimate that changes in all the policy instruments combined can explain up to 1.2% of the changes in export capabilities in the periods 2012-2015 and 2015-2018. We then use the econometric results to illustrate the potential impact of removing fossil fuel subsidies on the pattern of comparative advantage in carbon intensive industries. Furthermore, we extend our analysis to consider potential policy spillovers along the supply chain. The results suggest that carbon pricing policies compound along the domestic supply chain so that an industry's export competitiveness increases when its carbon intensive domestic suppliers face lower carbon prices or higher fossil fuel subsidies. We also find s ome l imited empirical support for supply chain spillovers of foreign carbon prices.
Keywords: F18; Q48; Q56; Q58; 330; Carbon Pricing; Fossil Fuel Subsidies; Fossil Fuel Taxes; Comparative Advantage; Competitiveness